HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN KETEPATAN PEMBERIAN MP-ASI PADA BAYI DIKELURAHAN TIGABALATA KECAMATAN JORLANG HATARAN KABUPATEN SIMALUNGUN TAHUN 2015 - devi c simbolon; Heru Santosa; Asfriyati . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTBreastfeeding supplementary food is a supplementary food other than breastmilk given to the baby after the baby is 6 months old. In addition to breastfeedingsupplementary food, breast milk should still be given to the baby, at least until 24months. The cause of the baby's growth disorders is due to the provision ofcomplementary feeding by mothers who do not conform with the precision timing,frequency, type, number of foodstuffs, and the weave. The objective of theresearch was to investigate the relation between knowledge and mother attitudewith the breastfeeding supplementary food in giving to the babies at theTigabalata village in 2015.This type of research is a survey of analytical by using cross sectionaldesign,the population in the study were all women who had a baby 24 months asmany as 57 infants and serve as the total sample. Data was obtained throughinterviews using a questionnaire and analyzed by chi-square test.From the results of the chi-square test (α <0.05), indicating there is asignificant relationship between the knowledge with accuracy gift weaning infantsobtained p = 0.002. And there is a significant relationship between the attitude ofa mother with the breastfeeding supplementary food to the babies obtained p =0.029.Expected to health workers who work at the health center Tiga Balata moreroutine counseling on appropriate complementary feeding to mothers personally.Also to mothers who have babies to more frequent follow Posyandu activities andcounseling are held in villages as well as increased knowledge and search forhealth information, especially the provision of complementary feeding.Keywords: Knowledge, Attitude, Breastfeeding Suplementary food